MEDIA SIMULASI PhET BERBASIS INKUIRI TERBIMBING MATERI GETARAN DAN GELOMBANG TERHADAP PENINGKATAN KETERAMPILAN PROSES SAINS PESERTA DIDIK - Ravalina Singka Subeki; Dyah Astriani; Ahmad Qosyim (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
The purpose of this study is to determine the use of PhET simulation media based on guided inquiry to improve science process skills students on vibration and wave material. The type of research contucted was Pre experiment with One Group Pretest Posttest as the research design. For research subject were student of VIII-D grade in SMP Negeri 1 Sidoarjo for academic year 2020/2021, totaling 32 students. Then, data collection methods include test sheets of science process skills based and response questionnaires. The results showed that the pretest and posttest score increased by 0,70 in the high category. While, the results of the students responses showed a high interest in the use of PhET simulation media based on guided inquiry for vibration and wave materials with a total average of 88,6%. The conclusion of the research is that the use of PhET simulation media based on guided inquiry can improve science process skills. And the implication of the research is that teachers can determine the competence of science process skills students, so that they can determine science learning that can improve science process skills.